The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0011128720926108
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Resting Heart Rate and Childhood Risk Factors in Predicting Convictions and Antisocial Personality Scores

Abstract: This article analyzes data collected in the Cambridge Study in Delinquent Development, which is a prospective longitudinal study of 411 London males from Ages 8 to 61. It aims to investigate interactions between Age 8 and Age 10 psychosocial risk factors and a biological factor (resting heart rate), measured at Age 18, in predicting convictions up to Age 61 and high antisocial personality scores at Ages 32 and 48 (combined). The present analyses suggest that a high resting heart rate acted as a protective fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…Farrington (2020b) then investigated interactions between RHR and childhood (age 8–10) risk factors in predicting all convictions up to age 61 and a measure of antisocial personality at ages 32 and 48 combined. The results showed that high RHR protected against the effects of harsh parental discipline, a depressed mother, and being difficult to discipline in predicting all convictions.…”
Section: Introductionmentioning
confidence: 99%
“…Farrington (2020b) then investigated interactions between RHR and childhood (age 8–10) risk factors in predicting all convictions up to age 61 and a measure of antisocial personality at ages 32 and 48 combined. The results showed that high RHR protected against the effects of harsh parental discipline, a depressed mother, and being difficult to discipline in predicting all convictions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also relevant that the majority of research addresses biological factors only as risk factors and not as potential protective factors that can moderate the influence of risks and buffer against undesirable behavioral outcome. For example, Farrington ( 2020 ) showed that high RHR had a protective function in the prediction of conviction and antisocial personality characteristics when the individuals had experienced childhood risk factors. In comparison to risk oriented research, the investigation of protective factors and mechanisms of antisocial behavior is less developed (Lösel and Farrington, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A second common theme is the need to examine interactions between biological, psychological, and social risk factors. Four of the studies found some evidence of interactions between biological and social risk factors (Cooke et al, 2020; Farrington, 2020; Fox et al, 2020; Portnoy et al, 2020). As demonstrated by these articles, neither biological, psychological, nor social risk factors alone are likely to explain the etiology of criminal behavior and related outcomes.…”
mentioning
confidence: 99%
“…Fox, Bozzay, & Verona (2020) examine gene × environment interactions in predicting psychopathy in adults. Farrington (2020) tests the interaction between resting heart rate and multiple psychosocial risk factors in predicting convictions and antisocial personality scores in males participating in the Cambridge Study in Delinquent Development. Portnoy, Raine, Rudo-Hutt, Gao, and Monk (2020) also test a biosocial interaction, studying whether the interaction between heart rate reactivity and neighborhood disadvantage predicts antisocial behavior in children.…”
mentioning
confidence: 99%
See 1 more Smart Citation